The new left revisited - McMillian, John Campbell; Buhle, Paul, 1944- (Critical perspectives on the past., 2003)
Starting with the premise that it is possible to say something significantly new about the 1960s and the New Left, the contributors to this volume trace the social roots, the various paths, and the legacies of the movement that set out to change America. As members of a younger generation of scholars, none of them (apart from Paul Buhle) has first-hand knowledge of the era. Their perspective as non-participants enables them to offer fresh interpretations of the regional and ideological differences that have been obscured in the standard histories and memoirs of the period. Reflecting the diver.